Financial scenario modelling: a study of UK universities. Issue 6 (2nd November 2021) - Cropper, Paul; Cowton, Christopher J.
ABSTRACT: Financial scenario modelling appears to offer the potential to help universities cope with an uncertain funding environment. By means of a questionnaire survey of UK universities, supported by interviews with members of finance departments, this paper explores the prevalence and construction of financial models used for scenario analysis. According to the findings, most universities undertake such modelling; but a minority do not, even though it is officially required. There is some variation in the purposes for which the models are constructed and in the sophistication of the approaches taken, but the overall impression is of a relatively straightforward approach, with spreadsheets generally viewed as having sufficient functionality to meet current strategic needs. There is no appetite for a standard template to be imposed or even offered by the funding councils. Sharing experience is likely to be a more welcome approach if growing pressures prompt finance departments to strengthen their modelling.